PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK DESAIN GRAFIS PADA KAOS MENURUT UNDANG-UNDANG NOMOR 31 TAHUN 2000 TENTANG DESAIN INDUSTRI (Studi Pada Penjual Kaos di Malioboro Yogyakarta) - Ezra Mayora Widiasari; Adi Sulistiyono (Fakultas Hukum Universitas Sebelas Maret, 2023)
This article aims to find out what are the problems that hamper legal protecting of rights holders in T-shirt graphic design according to law number 31 of 2000 concerning industrial design ( case study in T-shirt seller in Malioboro, Yogyakarta).The research methodology used is a non-doctrinal research method or Empirical research, which is researching secondary data at first, then continuing research on primary data in the field. The law of the Republic of Indonesia Number 30 of 2000 concerning Industrial Design which is protected a creator of graphic design. A graphic design is a one of creation must be protection. Especially for creator of design graphic. The result of protection for T-shit creator design graphic in Malioboro, Yogyakarta, is not protected optimally because there are defect in implementation and there are three inhibiting factors. Researchers getting conclusion that the implementation of protected for creator rights graphic design on t-shirt is not optimally and to harmful for creator and designer